Air operations in Israel's war against Hezbollah : learning from Lebanon and getting it right in Gaza - Lambeth, Benjamin S. (Rand Corporation monograph series., 2011)
In response to a surprise incursion by Hezbollah combatants into northern Israel and their abduction of two Israeli soldiers, Israel launched a campaign that included the most complex air offensive to have taken place in the history of the Israeli Air Force (IAF). Many believe that the inconclusive results of this war represent a "failure of air power." The author demonstrates that this conclusion is an oversimplification of a more complex reality. He assesses the main details associated with the Israeli Defense Forces' (IDF's) campaign against Hezbollah to correct the record regarding what Israeli air power did and did not accomplish (and promise to accomplish) in the course of contributing to that campaign. He considers IAF operations in the larger context of the numerous premises, constraints, and ultimate errors in both military and civilian leadership strategy choice that drove the Israeli government's decisionmaking throughout the counteroffensive. He also examines the IDF's more successful operation against the terrorist organization Hamas in the Gaza Strip in December 2008 and January 2009, to provide points of comparison and contrast in the IDF's conduct of the latter campaign based on lessons learned and assimilated from its earlier combat experience in Lebanon.--Publisher description.